Comparación de los factores internos que inciden en el metabolismo del CO2 en plantas C3 y C4 - Molina Cedeño, Pedro Alejandro (2021)
The Earth is facing two major threats, the first is global warming, which is reaching an alarming stage, and the second is the world population which is also expanding rapidly. Environmental factors affect the most fundamental biological process including photosynthesis and different metabolic pathways to assimilate CO2 from the environment. Therefore, the present study focused on characterizing the internal factors affecting CO2 metabolism of C3 and C4 plants. Consequently, these plants have different carbon assimilation, anatomical and biochemical characteristics. Most land plants, including important crops such as rice, soybean, wheat and potato, assimilate atmospheric CO2 via the Calvin cycle as a three-carbon (3C) compound, 3-phosphoglycerate (3-PGA), also known as the C3 pathway of photosynthesis. In this process, the enzyme ribulose-1,5-bisphosphate carboxylase/oxygenase (Rubisco) plays an important role in the assimilation of atmospheric CO2 and, under stress conditions, this enzyme has more affinity for O2, resulting in the opposite process to photosynthesis, photorespiration. However, during evolution, warm environments and plants with C4 photosynthesis evolved, with a series of distinct properties (in particular, the anatomy of the Kranz leaf and the division of the cycle between two cell types) that allowed the capture of CO2 in a 4C compound (Oxaloacetate) and its concentration in the vicinity of Rubisco, in order to reduce the oxygenase activity of that enzyme and, therefore, the rate of photorespiration.